Arts, Religion, and the Environment Exploring Nature's Texture - Bergmann, Sigurd; Clingerman, Forrest (Studies in Environmental Humanities, 2018)
Exploring Nature's Texture brings together a collection of internationally-known group of artists, theologians, anthropologists and philosophers to look at the imaginative possibilities of using the visual arts to address the breakdown of the human relationship with the environment. ; Readership: Scholars and students in theology/religious studies, art history, artists and curators, environmental humanities, environmental studies, philosophy, anthropology, environmental arts, architecture, sociology.